2020
DOI: 10.3390/molecules25081977
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Testing of Schinus molle (L.) Leaf Extracts and Fractions Followed by GC-MS Investigation of Biological Active Fractions

Abstract: Schinus molle (L.) is a dioecious plant of the Anacardiaceae family, originating in South America and currently widespread in many regions throughout the world. In this work leaf extracts and derived low-pressure column chromatography (LPCC) fractions of S. molle L. male and female plants were investigated for the antimicrobial activity. Leaf extracts were tested on microbes Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Enterococcus faecalis, Candida albicans and Bacillus subtilis. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
1
5
0
2
Order By: Relevance
“…Limonium avei (De Not.) Brullo and Erben [31]; Schinus molle (L.) [32]; Thymus vulgaris [28]; Crocus sativus L. [33]; Glycyrrhiza glabra [34]; Dianthus rupicola [20]; Lavandula angustifolia L. [35]; Hypericum taxa (Guttiferae) [36]; Fuscoporia torulosa (Basidiomycetes) [27]; Fuscoporia torulosa [27]; Thymus vulgaris [28]; Bupleurum fontanesii [37]; Crithmum maritimum [38]; Ferulago campestris [39]; Origanum onites and Thymus capitatus [40] Clostridium difficile 2 Angelica archangelica L. [41]; Echinophora spinosa (Apiaceae) [42] Clostridium perfringens 3 Angelica archangelica L. (Apiaceae) [41]; Satureja montana L. [43]; Echinophora spinosa (Apiaceae) [42] Table 1. Cont.…”
Section: Bacillus Cereus 17unclassified
See 2 more Smart Citations
“…Limonium avei (De Not.) Brullo and Erben [31]; Schinus molle (L.) [32]; Thymus vulgaris [28]; Crocus sativus L. [33]; Glycyrrhiza glabra [34]; Dianthus rupicola [20]; Lavandula angustifolia L. [35]; Hypericum taxa (Guttiferae) [36]; Fuscoporia torulosa (Basidiomycetes) [27]; Fuscoporia torulosa [27]; Thymus vulgaris [28]; Bupleurum fontanesii [37]; Crithmum maritimum [38]; Ferulago campestris [39]; Origanum onites and Thymus capitatus [40] Clostridium difficile 2 Angelica archangelica L. [41]; Echinophora spinosa (Apiaceae) [42] Clostridium perfringens 3 Angelica archangelica L. (Apiaceae) [41]; Satureja montana L. [43]; Echinophora spinosa (Apiaceae) [42] Table 1. Cont.…”
Section: Bacillus Cereus 17unclassified
“…Schinus molle (L.) [32]; Achillea moschata [17]; Angelica archangelica L. (Apiaceae) [41]; Rapa Catozza Napoletana (Brassica rapa L. var. rapa DC.)…”
Section: Bacterium (Gram+) Number Of Plant Species Plant Nameunclassified
See 1 more Smart Citation
“…The fruits secrete esters, alcohols, aldehydes, ketones, lactones, terpenoids and carotenoid derivatives 30 . Several studies have shown that the EO extracted from leaves of S molle exhibits anticancer, antioxidant, anti‐tumoral and antimicrobial properties 31‐33 …”
Section: Introductionmentioning
confidence: 99%
“…Schinus molle L., internationally commonly known as peruvian pepper, false pepper, American pepper, or pink pepper, is a perennial tree belonging to the Anacardiaceae family, which is native to subtropical regions of South and Central America [ 8 ]. In Peru, it is popularly known as molle (in Spanish) and its leaves and fruits exhibit anti-inflammatory, analgesic, antirheumatic, antibacterial, antiseptic, and repellent activity [ 9 ]. The essential oil of S. molle (leaves and fruits) exhibits biological activities such as antibacterial (gram-positive and gram-negative bacteria), antifungal, insecticidal, repellent, and cytotoxic activities [ 10 ].…”
Section: Introductionmentioning
confidence: 99%